2021
DOI: 10.1111/1759-7714.14210
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circCPA4 promotes tumorigenesis by regulating miR‐214‐3p/TGIF2 in lung cancer

Abstract: Background: Lung cancer is the most prevalent malignancy in adults. Circular RNA (circRNA) circCPA4 (hsa_circ_0082374) is highly expressed in non-small cell lung cancer (NSCLC). The purpose of this study was to explore the role and mechanism of circCPA4 in lung cancer. Methods: CircCPA4, linear CPA4, TGF-β-induced factor homeobox 2 (TGIF2), and microRNA-214-3p (miR-214-3p) levels were measured by real-time quantitative polymerase chain reaction (RT-qPCR). The protein levels of TGIF2, Beclin1, and p62 were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Additionally, our data aligned with the reports of high circCPA4 expression in NSCLC tissues and cells 27 . The current study provided evidence that knockdown of circCPA4 impeded the malignant progression of NSCLC cells in vitro, as well as in a mouse tumor model, corroborating existing literature on this topic 13 . The enhancement of glutamine metabolism is known to drive various cancer cell processes, and targeting glutamine metabolism has emerged as a potential therapeutic approach in cancer therapy 28 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Additionally, our data aligned with the reports of high circCPA4 expression in NSCLC tissues and cells 27 . The current study provided evidence that knockdown of circCPA4 impeded the malignant progression of NSCLC cells in vitro, as well as in a mouse tumor model, corroborating existing literature on this topic 13 . The enhancement of glutamine metabolism is known to drive various cancer cell processes, and targeting glutamine metabolism has emerged as a potential therapeutic approach in cancer therapy 28 .…”
Section: Discussionsupporting
confidence: 89%
“…27 The current study provided evidence that knockdown of circCPA4 impeded the malignant progression of NSCLC cells in vitro, as well as in a mouse tumor model, corroborating existing literature on this topic. 13 The enhancement of glutamine metabolism is known to drive various cancer cell processes, and targeting glutamine metabolism has emerged as a potential therapeutic approach in cancer therapy. 28 In this study, we found that circCPA4 knockdown repressed intracellular glutamine, glutamate and α-KG levels in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 , 8 circCPA4 has been elucidated to be abundant in cancers and involved in the biological activities of cancer cells. 9 , 10 , 11 However, its biological function in PC remains unclear. miRNAs are crucial in gene expression modification 12 and miRNAs can target specific mRNAs and regulate their expression, while circRNAs can act as a sponge for miRNAs and regulate their availability to targeted mRNAs.…”
Section: Introductionmentioning
confidence: 99%